2009
DOI: 10.1152/ajpcell.00049.2009
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of high glucose and free fatty acid on cardiomyocytes are mediated by connective tissue growth factor

Abstract: Wang X, McLennan SV, Allen TJ, Tsoutsman T, Semsarian C, Twigg SM. Adverse effects of high glucose and free fatty acid on cardiomyocytes are mediated by connective tissue growth factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…30, 31 In addition to stimulating collagen synthesis and causing fibroblast proliferation, 32 CTGF also induces hypertrophy and apoptosis in cardiomyocytes. 33 In this study, we found that CTGF expression was elevated in the atria of AF patients. We also demonstrated that after 1 h of Ang II perfusion, rat hearts rapidly expressed increased CTGF mRNA and protein expressions.…”
Section: Discussionmentioning
confidence: 54%
“…30, 31 In addition to stimulating collagen synthesis and causing fibroblast proliferation, 32 CTGF also induces hypertrophy and apoptosis in cardiomyocytes. 33 In this study, we found that CTGF expression was elevated in the atria of AF patients. We also demonstrated that after 1 h of Ang II perfusion, rat hearts rapidly expressed increased CTGF mRNA and protein expressions.…”
Section: Discussionmentioning
confidence: 54%
“…81 These CCN2 effects were shown to rely on the activity of the tyrosine kinase A receptor that has previously been implicated in CCN2-dependent signaling (Figure 1). 81 CCN2 silencing using small interfering RNA of activated primary cardiac fibroblasts resulted in strongly reduced expression of stretch-induced chemokines (Ccl2, Ccl7, and Ccl8), matrix metalloproteinases (MMP2 and MMP9), ECM (Col3a1), and a cell-to-cell contact protein (Cx43). 82 Ang-II-induced expression of hypertrophic marker genes or collagens was not affected by treatment with anti-CCN2 monoclonal antibodies, whereas anti-CCN2 monoclonal antibodies caused resistance to adverse LV remodeling and LV dysfunction in hearts resulting from pressure overload caused by thoracic aortic constriction.…”
Section: Ccn2mentioning
confidence: 82%
“…79,80 Expression of CCN2 mRNA is induced by both high glucose and palmitate in H9c2 cells and in mouse neonatal cardiomyocyte primary cultures. 81 Small interfering RNAs against CCN2 reduced the abilities of high glucose and palmitate to induce hypertrophy and apoptosis. 81 These CCN2 effects were shown to rely on the activity of the tyrosine kinase A receptor that has previously been implicated in CCN2-dependent signaling (Figure 1).…”
Section: Ccn2mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, experimental diabetes mellitus leads to upregulation of profibrotic genes and fibrosis in the myocardium [26,27]. In the heart, connective tissue growth factor also appears as a mediator of adverse effects of high glucose and fatty acids in cardiomyocytes [28]. Interestingly, connective tissue growth factor has also been implicated in the epithelial-to-mesenchymal transition of renal tubular epithelial cells, which contributes to the renal fibrosis associated with diabetic nephropathy [29].…”
Section: Insulin Resistance and Fibrosismentioning
confidence: 99%